Experiencia de alfabetización con los indios chocoes (2022)
eng: The experiences of U.S. and Panamanian professors in teaching Chocó Indians to read and write have produced excellent results. They have also shown the worth of starting this process through the Indian language, using spanish spelling by preference, and then going on to be the latter language. To do this, they first train some lndians to serve as "promotores" who in turn teach others to read in the two languages. Once the Indians have learned to read, their assimilation into the nation will become easier, as there are a great number of advantages for them to be obtained.